Інформаційна безпека організації як фактор посилення бренду роботодавця - Мазник, Ліана Валеріївна; Драган, Олена Іванівна (My University, 2023)
В статті розглядаються питання актуальності формування та посилення бренду роботодавця в умовах посилення конкурентної боротьби за таланти та зростаючих ризиків в сфері інформаційної безпеки в умовах повномасштабної війни. Авторами визначені ключові елементи, які є основою бренду роботодавця з урахуванням вимог інформаційної безпеки. Зазначено, що головним напрямком забезпечення інформаційної безпеки є створення комплексної системи захисту інформації, що передбачає комплекс і технічних та організаційних заходів. Розглянуті питання сертифікації систем управління інформаційною безпекою як індикатора ефективності управління бізнес-процесами організації, інформаційними ризиками, стійкості та надійності розвитку компанії. Запропоновано послідовність дій для впровадження стандартів інформаційної безпеки та систему метрик оцінки ефективності впровадження стандартів інформаційної безпеки як факторів посилення бренду роботодавця. В роботі обґрунтовано, що при формуванні ціннісної пропозиції роботодавця (EVP) доцільно додавати до набору переваг дотримання стандартів інформаційної безпеки. The article examines the relevance of forming and strengthening the employer's brand in the context of increased competition for talent and growing risks in the field of information security in the context of a full-scale war. The authors identified the key elements that are the basis of the employer brand, taking into account information security requirements. It is noted that the main direction of ensuring information security is the creation of a complex system of information protection, which includes a complex of technical and organizational measures. The issues of certification of information security management systems as an indicator of the effectiveness of management of the organization's business processes, information risks, stability, and reliability of the company's development are considered. A sequence of actions for the implementation of information security standards and a system of metrics for evaluating the effectiveness of information security standards as factors for strengthening the employer's brand are proposed. The paper substantiates that when forming the employer's value proposition (EVP) it is advisable to add compliance with information security standards to the set of advantages. For the implementation of information security standards in order to strengthen the company's employer brand, an algorithm is proposed, which consists of the following stages: 1. Assessment of the company's need for information security. 2. Determination of risk zones. 3. Development of an implementation plan. 4. Organization of training. 5. Creation of a checklist for compliance with information security standards in all divisions. To evaluate the effectiveness of the implementation of information security standards, the following metrics are proposed: 1. The number of security breaches. 2. Recovery time. 3. The number of employees who have undergone appropriate training. 4. Number of viruses and malware. Demonstrating a secure work environment and ensuring that employees' personal data is protected is an important aspect of an effective EVP that meets information security requirements.
Keywords: кафедра економіки праці та менеджменту; кафедра маркетингу; бренд роботодавця; інформаційна безпека; репутація; стандарти; комплексна система захисту інформації; система управління інформаційною безпекою; employer brand; information security; reputation; standards; comprehensive information protection system; information security management system